2018
DOI: 10.33369/jeet.2.1.22-27
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Directive Speech Acts by Searle Theory in “Sleeping Beauty” Movie Script

Abstract: This research aims to find out the types of Directive Speech Acts by the characters in “Sleeping Beauty” movie script based on the theory that proposed by Searle theory and analyze the types of directive speech acts that most frequently used in the movie script and the possible reason for it. The subject of the research was the script of the conversation between the characters. The type of this research is Descriptive Quantitative research. In this research, the researcher used documentation as the instrument.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 1 publication
0
12
2
1
Order By: Relevance
“…Furthermore, these slogans are a simple way to advertise the purpose and a school's mission especially in the students' building character. In contrast to previous papers, Della and Sembiring (2018), Tesaindra (2017) found that the most dominant type of directive speech act used was command type on the movie. This proves that context plays a very important role in the way of understanding any text like the directive illocutionary acts analysis in the school slogans.…”
Section: Commandingcontrasting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, these slogans are a simple way to advertise the purpose and a school's mission especially in the students' building character. In contrast to previous papers, Della and Sembiring (2018), Tesaindra (2017) found that the most dominant type of directive speech act used was command type on the movie. This proves that context plays a very important role in the way of understanding any text like the directive illocutionary acts analysis in the school slogans.…”
Section: Commandingcontrasting
confidence: 62%
“…There are some previous studies examining the directive speech acts (e.g. Della & Sembiring, 2018;Fitria, 2019;Oktoberia & Hamzah, 2012;Tesaindra, 2017). Mostly, the studies are more viewed from the perspective of the movies and their results are more dominated by the commanding type.…”
Section: Introductionmentioning
confidence: 99%
“…The central point of pragmatics is speech acts. The speech act is the study of the meaning and function of an utterance (Della & Sembiring, 2018).…”
Section: Anggraeni Indrayani Soemantrimentioning
confidence: 99%
“…It is an attempt to persue truth through the methods of study, observation, comparison and experiment. In other words, research is simply gathering the information you need to answer a question and thereby help you solve a problem (Della & Sembiring, 2018).…”
Section: Methodsmentioning
confidence: 99%